A Case Study on Domino’s Business Survival Strategy During the Covid-19 Pandemic - Kumar, Navaneetha; Singh, Padmalini; Shan, Liew Pei; Kee, Daisy Mui Hung; Mei, Lee Tze; Ying, Ngai Wan; Zhi, Ooi Yu (International Journal of Tourism and Hospitality in Asia Pasific, 2021)
COVID-19 pandemic has spread around the world and affected the development of economic countries. Some countries and states are under hotspot areas. During the lockdown period, many organizations were forced to close their businesses, causing economic recession. In addition, many companies have seen a sharp decline in their sales and affecting their profits. Due to the COVID-19 pandemic, many restaurants have started their service with takeaway or delivery, however they still unable to sustain their business, especially the small and medium-sized enterprises (MSMEs). This study aims to study the strategies used by Domino’s in sustaining their business during the COVID-19 pandemic. Quantitative method was used in this study and the data were collected within 2 weeks through the online distribution by using Google Form. The results showed the strategies used by Domino’s company for business survival during the COVID-19 pandemic are promotions and provided quality foods and there is a significant relationship between promotions and the preference for Domino’s Pizza.